Iron-based compounds coordinated with phospho-polymers as biocompatible probes for dual 31P/1H magnetic resonance imaging and spectroscopy - Kracíková, Lucie; Androvič, Ladislav; Červený, David; Jirát-Ziółkowska, Natalia; Babič, Michal; Švábová, Monika; Jirák, Daniel; Laga, Richard (Scientific reports, 2024)
In this work, we present the synthesis and evaluation of magnetic resonance (MR) properties of novel phosphorus/iron-containing probes for dual 31P and 1H MR imaging and spectroscopy (MRI and MRS). The presented probes are composed of biocompatible semitelechelic and multivalent phospho-polymers based on poly(2-methacryloyloxyethyl phosphorylcholine) (pMPC) coordinated with small paramagnetic Fe3+ ions or superparamagnetic maghemite (γ-Fe2O3) nanoparticles via deferoxamine group linked to the end or along the polymer chains. All probes provided very short 1H T1 and T2 relaxation times even at low iron concentrations. The presence of iron had a significant impact on the shortening of 31P relaxation, with the effect being more pronounced for probes based on γ-Fe2O3 and multivalent polymer. While the water-soluble probe having one Fe3+ ion per polymer chain was satisfactorily visualized by both 31P-MRS and 31P-MRI, the probe with multiple Fe3+ ions could only be detected by 31P-MRS, and the probes consisting of γ-Fe2O3 nanoparticles could not be imaged by either technique due to their ultra-short 31P relaxations. In this proof-of-principle study performed on phantoms at a clinically relevant magnetic fields, we demonstrated how the different forms and concentrations of iron affect both the 1H MR signal of the surrounding water molecules and the 31P MR signal of the phospho-polymer probe. Thus, this double contrast can be exploited to simultaneously visualize body anatomy and monitor probe biodistribution.
Keywords: magnetická rezonanční tomografie; Polymers; Tissue Distribution; Magnetic Resonance Imaging; Iron; železo; tkáňová distribuce; Water; polymery; Magnetic Resonance Spectroscopy; magnetická rezonanční spektroskopie; voda